1991
DOI: 10.1007/bf00231740
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal hyperthyroidism disrupts hippocampal LTP and spatial learning

Abstract: Excess thyroid hormone at an early stage of development produces marked neurochemical and morphological alterations in the rat hippocampal formation. In order to better understand the functional significance of these changes, we tested adult rats treated neonatally with triiodothyronine (T3), and their control litter mates, in a spatial learning task and for the induction of long-term potentiation (LTP) in the dentate gyrus (DG) of the hippocampal formation. The T3-treated rats were significantly impaired in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1
4

Year Published

1992
1992
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 27 publications
2
21
1
4
Order By: Relevance
“…In parallel with our findings, it was reported that the efficacy of LTP induction was significantly attenuated in T3-treated rats, indicating that neonatal hyperthyroidism disturbs LTP in the DG of the hippocampal formation [36]. Furthermore, local T4 microinjection in the DG in normothyroid and propylthiouracil-treated rats produced an immediate and long-lasting decrease in the PS amplitude recorded from the DG following stimulation of the medial perforant pathway [51].…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…In parallel with our findings, it was reported that the efficacy of LTP induction was significantly attenuated in T3-treated rats, indicating that neonatal hyperthyroidism disturbs LTP in the DG of the hippocampal formation [36]. Furthermore, local T4 microinjection in the DG in normothyroid and propylthiouracil-treated rats produced an immediate and long-lasting decrease in the PS amplitude recorded from the DG following stimulation of the medial perforant pathway [51].…”
Section: Discussionsupporting
confidence: 71%
“…It would be expected from the observed impairment of PTP and LTP in hyperthyroidism that hyperthyroid rats would perform worse on spatial tasks than control rats, as seen in the present study. In accordance with our findings, it was reported that T3-treated rats were significantly impaired in their performance on a spatial task (Y-maze) and showed attenuated LTP induction when compared with their matched controls [36]. These findings do not agree with the study of Smith et al [55], however, who reported that the group receiving the highest dose of T4 (5 mg) showed improved performances on day 4 [55].…”
Section: Discussioncontrasting
confidence: 41%
See 2 more Smart Citations
“…Neonatal gelişim aşamala-rında aşırı tiroid hormonunun sıçan hipokampal oluşu-munda belirgin nörokimyasal ve morfolojik değişiklikler oluşturduğu gösterilmiştir. Bu değişikliklerin fonksiyonel önemini anlamak için, uzamsal öğrenme ve uzun dönemli güçlenme (UDG) çalışmasında, T3 verilen hayvanlarda UDG yanıtlarının azaldığı ve neonatal hipertiroidizmde hipokampal UDG'nin bozulduğu gösterilmiştir (31). Hipotiroidili sıçanlarda da öğrenme ve UDG'de bozulma olduğu bildirilmiştir (32)ve bu hipotiroidili sıçanlar tiroid hormonu ile tedavi edildiğinde UDG'deki bu bozukluğun düzeldiği gözlenmiştir.…”
Section: Tartışma Ve Sonuçunclassified